Development of power conditioning circuit for reliable use of battery on automated guided vehicle - Tan, Wei Lun (2023)
This study focuses on the development of a hybrid energy storage system (HESS) for an automated guided vehicle (AGV) used in indoor navigation. The AGV relies on a 3000mAh LiPo battery as its primary power source, which experiences rapid swelling, leading to increased operational costs due to the replacement of the battery occurs every 8 months on average. The inrush current required by the battery during the start-up of inductive loads such as the AGV motor and robotic arm on board. To achieve this, a HESS which combined a super-capacitor and the LiPo battery is proposed. During starting of the inductive load, the supercapacitor works in parallel with the LiPo battery to power the load, reducing the current required by the battery. During normal running conditions when the current required is much lower, only the LiPo battery will provides the power. When the supercapacitor's voltage level is low which is around 12.5V, it is connected parallel to the LiPo battery through a boost converter for charging. This HESS approach effectively reduces the inrush current experienced by the LiPo battery during AGV start-up, thus minimizing swelling of the battery. The performance of the proposed HESS is evaluated experimentally, and the results demonstrate its effectiveness in reducing the current stress experienced by the LiPo battery.